2017
DOI: 10.21548/38-2-1546
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maturity and Vineyard Location on Free and Bound Aroma Compounds of Grapes from the País Cultivar

Abstract: Some of the volatile compounds present in grapes give wine is its unique and genuine characteristics. "Terroir" and berry maturity are considered to be the main influences on the expression of these characteristics. This work was undertaken to establish the specific characteristics that define Vitis vinifera cv. País, based on its aromatic profile and free and bound compounds (glycosides), and to assess the effects of location and maturity. Free and bound volatile compounds presented significant differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 29 publications
1
27
1
Order By: Relevance
“…Commercial wines were also studied. Ubeda et al . reported that Carignan wines from sites closer to the Andes Mountains showed significantly lower ester and acid content.…”
Section: Minority and Autochthonous Varietiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Commercial wines were also studied. Ubeda et al . reported that Carignan wines from sites closer to the Andes Mountains showed significantly lower ester and acid content.…”
Section: Minority and Autochthonous Varietiesmentioning
confidence: 99%
“…Vitispiranes were also identified as the best C 13 -norisoprenoids aging markers for young sparkling wines, and time of aging on lees affected mostly esters and terpenes. 42 On the other hand, Úbeda et al 24 studied the influence of ripening and location on free and bound aroma of País grapes. These authors reported that, during ripening, the concentration of aroma precursors increased in the different locations.…”
Section: Listán Prietomentioning
confidence: 99%
See 3 more Smart Citations